2023
DOI: 10.1111/ipd.13095
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of panoramic radiographs in children using age‐based prevalence of dental anomalies and pathologies

Ritu Mohan,
Chaitanya P. Puranik,
Pickett Kaci
et al.

Abstract: BackgroundPanoramic radiographs (PRs) are used in the detection and diagnosis of developmental dental anomalies and pathologies (DDAPs) in children.AimThe primary objective of this observational cohort study was to evaluate the age‐based prevalence of DDAP on PRs, whereas the secondary objective was to determine a threshold age for the detection of DDAP to provide supportive evidence for the prescription of PR in paediatric dental practice.DesignThe study examined diagnostic PRs from 581 subjects aged 6 to 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In this study, the highest finding was related to the impacted tooth (19.6%), and the lowest finding was related to dilacerations (0.39%) of the tooth root (14). Mohan et al examined 581 panoramic radiographs of American patients with an age range of 6-19 years, and the results showed that 74% of patients had at least one case of DA (15). In the study of 1200 panoramic images of orthodontic patients with an age range of 7 -17 years in Greek people by Pallikaraki et al, the prevalence of DAs was observed in 16.92% of people.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest finding was related to the impacted tooth (19.6%), and the lowest finding was related to dilacerations (0.39%) of the tooth root (14). Mohan et al examined 581 panoramic radiographs of American patients with an age range of 6-19 years, and the results showed that 74% of patients had at least one case of DA (15). In the study of 1200 panoramic images of orthodontic patients with an age range of 7 -17 years in Greek people by Pallikaraki et al, the prevalence of DAs was observed in 16.92% of people.…”
Section: Discussionmentioning
confidence: 99%